Ceramics from the North Church in Old Dongola revisited - Katarzyna de Lellis-Danys (Polish Archaeology in the Mediterranean)
The paper seeks to reexamine the ceramics unearthed from the North Church in Old Dongola. These findings are placed within the context of the terminal phase of Christianity in the capital of the Kingdom of Makuria. Examples of liturgical implements found in situ inside this Dongolese church provide a rare glimpse into the Nubian Liturgy. The paper incorporates new assessments of the ceramic chronology drawing on the recent findings of the UMMA project. Many vessels recovered in the 1980s are currently housed in the National Museum in Warsaw, presenting a unique and advantageous opportunity for their in-depth study and analysis. Consequently, they offer a fresh perspective on Old Dongola’s Late and Terminal Christian phases.